2021
DOI: 10.3390/cancers13081978
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Reader Agreement of Diffusion-Weighted Magnetic Resonance Imaging for Breast Cancer Detection: A Multi-Reader Retrospective Study

Abstract: Purpose: In order to evaluate the use of un-enhanced magnetic resonance imaging (MRI) for detecting breast cancer, we evaluated the accuracy and the agreement of diffusion-weighted imaging (DWI) through the inter-reader reproducibility between expert and non-expert readers. Material and Methods: Consecutive breast MRI performed in a single centre were retrospectively evaluated by four radiologists with different levels of experience. The per-breast standard of reference was the histological diagnosis from need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
5
9
1
Order By: Relevance
“…Image processing in the medical field is also used with great results for other types of image. For example in [ 25 , 26 ] a diffusion-weighted magnetic resonance imaging is discussed for breast and lung cancer detection. Reference [ 27 ] presented a survey of deep learning algorithms used in medical applications.…”
Section: Related Workmentioning
confidence: 99%
“…Image processing in the medical field is also used with great results for other types of image. For example in [ 25 , 26 ] a diffusion-weighted magnetic resonance imaging is discussed for breast and lung cancer detection. Reference [ 27 ] presented a survey of deep learning algorithms used in medical applications.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast to fatty breasts, dense breasts did not affect lesion detectability and ADC values [ 75 ]. It was found that for DWI, expert-level readers are necessary for reaching good results [ 76 ], because the detection and avoidance of areas affected by artefacts is important for parameter analysis and requires some experience. In general, DWI is not suited for patients with implants and in case of small lesions, which is a potential source of bias.…”
Section: Discussionmentioning
confidence: 99%
“…Image acquisition details of our 1.5 T MRI scanner protocol are reported in the Table S1 [ 19 , 20 ]. The dynamic study consisted of three-dimensional T1-w gradient-echo sequences acquired once before and five times after intravenous administration of 0.1 mmol/kg of a gadolinium chelate at 90 s temporal resolution.…”
Section: Methodsmentioning
confidence: 99%